Surgical strategy in a patient with an aggressive tumor of the gastrointestinal tract in the fourth portion of the duodenum - Tomás Ariel Lombardo Vaillant (Medisur)
Gastrointestinal stromal tumors are rare tumors and correspond to 1% of all gastrointestinal neoplasms; duodenal location only represents between 3-5%. This case report was made for disclosing the surgical strategy followed in a patient with invasive gastrointestinal stromal tumors (>10 cm) of atypical location in the duodenum fourth portion. Hospitalization was due to abdominal tumor and anemia. The clinical exercise consisted of identifying a left abdominal mass with lumbar contact. The diagnostic tests performed were: blood chemistry tests, abdominal ultrasound, computerized axial tomography, and digestive endoscopy with biopsy that confirmed the diagnosis. The surgical procedure was resection of the duodenum fourth portion and the first jejunal loops, with restoration of intestinal function through duodenum (second portion) lateral jejunostomy. The surgery was interrupted due to the patient's hemodynamic instability, and four days later he was taken back to the operating room due to peritonitis, with pus coming out of the abdominal drains, which was resolved by washing the cavity. Morbidity was accompanied by a pancreatic fistula. In the third surgical time, resection of the residual tumor, left nephrectomy, and control of the pancreatic fistula were performed. After one year the patient is free of tumor disease. The management strategy in patients with atypically located gastrointestinal stromal tumors represents a challenge for the surgeon as a member of the multidisciplinary group and depends on the extent of the tumor, the patient's condition, and the surgical team timely management.